Unearthing the Disturbing Ghosts of Postcolonial LandsThat Linger After the Sermon (Homiletic, 2024)
What lingers over a wounded community after preaching? This paper argues that the disturbing ghosts of postcolonial lands linger in the pulpit and haunt the wounded hearers after the sermon. Preachers should not only acknowledge but also preach about these ghosts whose presence are found in the Bible and in Christ. Mirroring the features of the ghosts, such preaching, which I term haunto-postcolonial preaching, disrupts the conventional notions of linear time and segregated space and connects the ghosts to the hearers and the Bible. Its goal is to create a haunting space in the pulpit, unearthing unresolved postcolonial trauma to bring rupture to the existing oppressive structures in the church and society. By allowing the ghosts to haunt the congregation about a lost or a reality yet-to-be-attained, preachers invite their hearers to reimagine and pursue a better and just society beyond the sermon where the unappeased souls can be consoled.